Cognitive effort in metaphor translation: An eye-tracking and key-logging study - Annette Camilla Sjørup (Copenhagen Business School (CBS), 2013)
This thesis, titled Cognitive effort in metaphor translation – an eye-tracking and key-logging study, is an empirical investigation of professional translators' cognitive effort during metaphor translation. Metaphors are defined as expressions in which one concept is used to characterise another concept, such as Peter is a wolf in which the characteristics of the wolf are used to define Peter. As a point of departure, the thesis adopts the direct access view of metaphors in which metaphors are regarded as unambiguous expressions which are interpreted as metaphors directly. Metaphors have primarily been researched in monolingual studies such as Glucksberg (2001) and Inhoff et al. (1984), who investigated how metaphors are processed and the cognitive effort required for this processing compared with literal expressions. The conclusion to their studies was that metaphors were not more cognitively effortful to process than literal expressions and that they were not necessarily more ambiguous either. Dagut (1987) and Newmark (1985, 1988) discussed metaphors from a translation perspective in which they regarded metaphors as a particular translation problem. Trim (2007) argued that the translatability of metaphors was related to their language-specific saliency. Neither Dagut, Newmark or Trim was empirical in his methodology, and the purpose of this thesis was to bridge the gap between the empirical methodology used in metaphor comprehension research and the more qualitative methodology used in metaphor translation research.
hdl:10398/8698
Keywords: 650